A Sorocabana Railway Company: a relação de uma empresa ferroviária privada com as diretrizes governamentais (1907-1919) - Corrêa, Lucas Mariani [UNESP] (2014)
On the propulsion of progress in Brazil Empire, at the 19th century, appear the first railroads. In 1875, crop out the Sorocabana Railway. During the early years of the Republic, São Paulo’s state government, through the Agriculture, Trade and Public Works Department, initiate to develop proposals to coordinate of the railroads and their expansion in the state in favor of the state’s guidelines of territory occupation and economical boost. Even during these years, in 1907, the Sorocabana will be lease by a businessmen group, represented by Percival Farquhar, becoming part of a holding. During the years under private management, from 1907 to 1919, many changes occurred on governmental proposals, even campaigns against this group domain on the railway activity. These facts lead to a contract rupture and the enterprise goes back to the public administration. Considering all this, our research goal is, first of all, to analyze which was the governmental proposals and guidelines, through the Agriculture Department, about the railways. Second, to comprise the involvement and relationship of the Sorocabana Railway Company with such guidelines. We use as research sources the Annual Reports of the Agriculture, Trade and Public Works Department; the Reports of the State’s president; reports of the company; also the administrative documents and others documents which involves our object